Некоторые аспекты проблематики психологии музыкального творчества и восприятия музыки - Гагикович Гянджумян, Иафшэдгар (Musical Armenia, 2010)
Singer, composer, graduate of Yerevan State Conservatory after Komitas. Edgar Gagik Gyanjumyan’s “Some aspects of problems of music psychology and music perception of musical work” article is a reference to music’s creative, psychology of music perception: composer-performer- listener trinity’s problem causing questions. The author illustrates it with analyses and from the viewpoint of interrelation among the psychological spheres of music refers to the conclusions of famous musicologists meanwhile stating his own opinion.